2021
DOI: 10.1177/00045632211004995
|View full text |Cite
|
Sign up to set email alerts
|

The use of whole blood capillary samples to measure 15 analytes for a home-collect biochemistry service during the SARS-CoV-2 pandemic: A proposed model from North West London Pathology

Abstract: Background The COVID-19 pandemic has drastically changed the delivery of secondary care services. Self-collection of capillary blood at home can facilitate the monitoring of patients with chronic disease to support virtual clinics while mitigating the risk of SARS-CoV-2 infection and transmission. Objective To investigate the comparability of whole blood capillary and plasma venous samples for 15 routinely used biochemical analytes and to develop and pilot a use-friendly home-collection kit to support virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 20 publications
6
30
0
Order By: Relevance
“…Good concordance has been reported in the literature for HbA 1c measured in capillary and venous blood samples using both dried blood spot devices and collection tubes 9,16–19 . Two previous studies reported that 69.2% and 70% of participants, respectively, would use a remote HbA 1c service if available or recommend this service 1,16 . Our study gave similar results with over three quarters of respondents (75.4% [43/57]) reporting that they would use the remote HbA 1c service routinely if available.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Good concordance has been reported in the literature for HbA 1c measured in capillary and venous blood samples using both dried blood spot devices and collection tubes 9,16–19 . Two previous studies reported that 69.2% and 70% of participants, respectively, would use a remote HbA 1c service if available or recommend this service 1,16 . Our study gave similar results with over three quarters of respondents (75.4% [43/57]) reporting that they would use the remote HbA 1c service routinely if available.…”
Section: Discussionsupporting
confidence: 85%
“…9,[16][17][18][19] Two previous studies reported that 69.2% and 70% of participants, respectively, would use a remote HbA 1c service if available or recommend this service. 1,16 Our study gave similar results with over three quarters of respondents (75.4% [43/57]) reporting that they would use the remote HbA 1c service routinely if available.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As people with diabetes are considered clinically vulnerable, exposure to COVID is best minimised where safe and possible. The pandemic saw further innovations to facilitate virtual diabetes outpatient consultations, such as home collection of capillary blood samples for HbA 1c and creatinine and urine for microalbumin measurement which are then posted by the patient to the laboratory 15 . These advances should serve as a stimulus for further training in the use of newer remote diabetes technologies; trainees could then support their incorporation into diabetes care in the community.…”
Section: Solutions and Opportunities For Changementioning
confidence: 99%